1995
DOI: 10.1002/path.1711770212
|View full text |Cite
|
Sign up to set email alerts
|

A megakaryocyte analysis of the bone marrow in patients with myelodysplastic syndrome, myeloproliferative disorder and allied disorders

Abstract: A morphometric analysis was performed on aspirate clots of bone marrow to identify the presence of atypical megakaryocytes after immunohistological staining with a monoclonal antibody against Factor VIII. This study included cases of myelodysplastic syndrome (MDS), myeloproliferative disorder (MPD), aplastic anaemia (AA), idiopathic thrombocytopenic purpura (ITP), chronic myelogenous leukaemia (CML), and control cases free from any haematological disease. Quantitative and qualitative abnormalities of megakaryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Such changes include an increase in microMK numbers, the predominance of MKs with cloud-shaped nuclei, and a decrease in both cytoplasmic area and the ratio of nuclear area to total area. These changes are characteristic of the state of dysmegakaryocytopoiesis reported in myelodysplastic syndromes 19 and in HIV infection. 2,28 Proliferation of reticulin fibers is also a common finding in this type of pathology.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Such changes include an increase in microMK numbers, the predominance of MKs with cloud-shaped nuclei, and a decrease in both cytoplasmic area and the ratio of nuclear area to total area. These changes are characteristic of the state of dysmegakaryocytopoiesis reported in myelodysplastic syndromes 19 and in HIV infection. 2,28 Proliferation of reticulin fibers is also a common finding in this type of pathology.…”
Section: Discussionmentioning
confidence: 93%
“…2,28 Proliferation of reticulin fibers is also a common finding in this type of pathology. 19,30 Impaired megakaryocytopoiesis in CSF may be related to various events taking place during the course of the disease. Chief among these are 1) the infection of stromal cells, mainly macrophages and reticular cells, both of which play a major role in regulating hematopoiesis in general and megakaryocytopoiesis in particular, through soluble chemical factors 1,13,32,33 and 2) depletion of T lymphocytes, which are also involved in modulating hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, these features are not present in all cases. Patients with chronic ITP, in particular, often do not have increased megakaryocyte concentrations (27,28) and exhibit decreased concentrations of megakaryocyte colonyforming units (CFU-MK) in megakaryocyte progenitor assays (29). Many of these patients have been shown to have antiplatelet antibodies that also react with megakaryocytes in the bone marrow and can inhibit their proliferation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [14,19] ever reported decreased ploidy (population was the largest in the 8N, not as the 16N in normal controls) in ordinary morphological recognized megakaryocytes on MDS marrow smears by measuring nuclear DNA content. But for micro-megakaryocytes (defined by CD61 sorting and CD41 restaining, which usually be ignored under ordinary staining), the 2N ploidy were in the absolutely ascendant, which represented the morphological immature and functional dysplasia of MDS megakaryocytes responsible for clinical dependence on platelet transfusion for reduced ploidy of megakaryocytes are associated with decreased rate of platelet production [26].…”
Section: Discussionmentioning
confidence: 97%